Primary stromal sarcomas of the breast: Case series on a rare entity - Ghosh Sengupta, Soumita; Bidisha Chakraborty; Kaushik Saha; Raychaudhuri, Gargi (Asian Journal of Medical Sciences, 2024)
Primary breast stromal sarcomas are rare entities arising from connective tissue within the breast, accounting for <5% of all soft tissue sarcomas and <1% of malignant breast tumors. Primary breast sarcomas are locally aggressive tumors and should be differentiated from malignant phyllodes tumor and metaplastic carcinoma of the breast, which are close mimickers. Here we present 4 cases of primary breast sarcoma that we found over the course of 7 years in our institution who presented with a breast lump. Mastectomy was performed, and they were diagnosed as primary stromal sarcoma of the breast.